Assesment of Occupational Stressor and Stress Response among Election Officers (KPPS) in 2019 - Dewi Sumaryani Soemarko; Muhammad Ilyas; Martha Landauw; Nuri Purwito Adi; Levina Chandra Khoe (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Introduction: The 2019 general election in Indonesia was the first general election to be held simultaneously and election officers (KPPS) had to complete the vote count on the same day with additional ballot papers. This situation caused high mortality and morbidity among KPPS officers due to stress and fatigue caused by job overload. This study was aimed to explore the factors related stress response in 2019 election KPPS officersMethods: A cross-sectional study design was conducted to the issue under the study included 80 data of KPPS officers at Polling Station (TPS) in Jakarta, Banten, and Yogyakarta. Occupational stressor and stress response was assesed with NBJSQ bahasa Indonesia. Multiple logistic regression models were used to explore factors associated with stress response.Results: The most perceived occupational stressor experienced by the 2019 General Election KPPS officers in this study were quantitative job overload (47,5%).The stress response that occurred in the 2019 General Election KPPS officers in this study was fatigue (17.5%). There was no relationship between occupational stressor and individual factors with stress response (p>0.05)Conclusion: This study showed that quantitative job overload was a major occupational stressor among KPPS officers in general election 2019. The stressor can trigger the incidence of heart attacks in predisposed individuals.